2015
DOI: 10.1016/j.ntt.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal immune challenge in rats: Effects of polyinosinic–polycytidylic acid on spatial learning, prepulse inhibition, conditioned fear, and responses to MK-801 and amphetamine

Abstract: Prenatal maternal immune activation increases risk for schizophrenia and/or autism. Previous data suggest that maternal weight change in response to the immune activator polyinosinic-polycytidylic (Poly IC) in rats influences the severity of effect in the offspring as does the exposure period. We treated gravid Sprague-Dawley rats from E14-18 with 8 mg/kg/day Poly IC or saline. The Poly IC group was divided into those that gained the least weight or lost (Poly IC (L)) and those that gained the most (Poly IC (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 80 publications
(140 reference statements)
11
46
2
Order By: Relevance
“…Notably, the present results show no difference between polyI:C and saline offspring during the initial nonmatching-tosample phase of the OST, which has a working memory component. Thus, our lack of effect with odor stimuli is consistent with the findings of Vorhees et al (2015) using a spatial matching-to-sample task. When the polyI:C-offspring were presented with the more challenging OST, deficits in task acquisition and performance emerged, consistent with impaired working memory capacity.…”
Section: Short-term Effects Of Polyi:c Treatment On Pregnant Damssupporting
confidence: 89%
See 2 more Smart Citations
“…Notably, the present results show no difference between polyI:C and saline offspring during the initial nonmatching-tosample phase of the OST, which has a working memory component. Thus, our lack of effect with odor stimuli is consistent with the findings of Vorhees et al (2015) using a spatial matching-to-sample task. When the polyI:C-offspring were presented with the more challenging OST, deficits in task acquisition and performance emerged, consistent with impaired working memory capacity.…”
Section: Short-term Effects Of Polyi:c Treatment On Pregnant Damssupporting
confidence: 89%
“…PolyI:C offspring are impaired on the OST Some previous studies have shown impaired working memory in the offspring of polyI:C-treated mice (Bitanihirwe et al 2010;Meyer et al 2005;Richetto et al 2013;2014); however, others have failed to see effects in young adult mice tested at short delays (Krstic et al 2012;Meyer et al 2005) and rats (Vorhees et al 2015). Notably, the present results show no difference between polyI:C and saline offspring during the initial nonmatching-tosample phase of the OST, which has a working memory component.…”
Section: Short-term Effects Of Polyi:c Treatment On Pregnant Damscontrasting
confidence: 76%
See 1 more Smart Citation
“…It should be noted here that male specific effects of poly-I:C on PPI occurred when offspring were exposed at GD9, while femalespecific PPI deficits were found when exposed to poly-I:C at GD14 -therefore the timing of infection may impact the male and female developing brain differently. Vorhees et al also found male specific deficits in fear-potentiated memory (cue conditioned freezing) in the offspring of poly-I:C exposed rats, but only following a repeated dosing regimen of poly-I:C injections from gestational day 14-18, while a single injection at day 14 had no such effect on the offspring (Vorhees et al 2012;Vorhees et al 2015). However, spatial memory, as assessed using a spontaneous alternation paradigm in the Y-maze, was specifically disrupted in female mouse offspring exposed to poly-I:C (5mk/kg i.p., GD9, n=5-8/group) (O'Leary et al 2014).…”
Section: Prenatal Immune Challenged Modelmentioning
confidence: 97%
“…However, high etiological validity can come at a cost. When measuring cognition, testing may be confounded by differences in learning (Vorhees et al 2012;Vorhees et al 2015). In addition, these models often produce a variety of nonspecific and diverse neurological changes, thus preventing the study of isolated systems (Hadar et al 2015).…”
Section: Validity Of the Acute Mk-801 Modelmentioning
confidence: 99%